ANALISIS PERILAKU GAYA KEPEMIMPINAN OTORITER TERHADAP KEPUASAN KERJA PADA GENERASI Z DAN MILENIAL: Systematic Literature Review - Ida Ayu Vidya Jyoti Pidada; Faniea Fadwa Putri; Abiyasa Hamdan Ismugono (SINERGI : Jurnal Riset Ilmiah, 2026)
In implementing a company's work program, leadership significantly influences the company's performance and work situation in implementing business programs that will be implemented in an integrated system with employees. The implementation of Indonesian leadership styles varies greatly. One leadership style used is authoritarian leadership. Authoritarian leadership is a bureaucratic and one-way leadership style. The influence of this leadership certainly has an impact on employee job satisfaction. The objectives of this study were: 1) Analyze the behavior of authoritarian leadership style on job satisfaction in Generation Z; 2) Analyze the behavior of authoritarian leadership style on job satisfaction in the millennial generation. The research method used was a Systematic Literature Review taken from reputable journals SINTA, SCOPUS, and non-reputable journals. The results of the study from the journal screening results, job satisfaction in Generation Z tends to decrease because this generation has characteristics that lead to flexibility. This is reinforced by the easy decline in work motivation if their participation is not meaningful to the company. Meanwhile, the millennial generation is more tolerant of organizational structures and has the ambition to actively participate in the work environment.